Steelmaking - Shamsuddin M. (My University, 2025)
Steel is an alloy of iron and one or more element(s), namely carbon, nickel, chromium, manganese, vanadium, molybdenum, tungsten, and so on. Chemically, steels may be classified in two groups: plain carbon steels and alloy steels. The former comprises the alloys of iron and carbon, whereas the latter contains one or more elements in addition to carbon. The alloying elements improve the mechanical, magnetic and electrical properties, as well as the corrosion resistance of steels. Impurities like Si, Mn, S, P, Al, and O are invariably present in steels due to their association in pig iron obtained by reduction smelting of iron ore with coke and lime in the blast furnace. Essentially, steelmaking is the conversion of molten pig iron (hot metal) containing variable amounts of 4.0–4.5% carbon, 0.4–1.5% silicon, 0.15–1.5% manganese, 0.05–2.5% phosphorus (normally between 0.06 and 0.25%), and 0.15% sulfur (normally between 0.05 and 0.08%) to steel containing about 1% of controlled amount of impurities by preferential oxidation. Alternatively, steel can be produced from solid sponge iron obtained by solid-state reduction of iron ore in the shaft furnace or retort. Thus, basically two routes are adopted in the production of steels. The first one employs the basic oxygen furnace (BOF – LD/Q-BOP/Hybrid converters) for treatment of hot metal, and the second route uses the electric arc furnace (EAF) to treat steel scrap/sponge iron or direct reduced iron (DRI). Electric arc or induction furnaces are generally used in the production of alloy steels. Pig iron contains a total of about 10% of C, Si, Mn, P, S, and so on as impurities, whereas sponge iron contains gangue oxides of iron ore, such as Al2O3, SiO2, CaO, and MgO. The amount and number of impurities depend on the quality of the iron ore, coke, and lime stone used in smelting. The molten pig iron is refined to molten steel under oxidizing conditions using iron ore and/or oxygen. On the other hand, scrap and sponge iron are melted in electric furnaces and refined for steel production. © 2021, The Minerals, Metals & Materials Society.